Competing in (and out of) transition economies - Mutlu, C.; Zhan, W.; Peng, Mike; Lin, Z. (Springer New York LLC, 2015)
Transition economies have become a new frontier for multinational enterprises (MNEs). This has introduced a highly dynamic competitive environment for domestic firms operating with such less developed institutions, especially those facing the threat of MNEs with superior capabilities. Drawing on the awareness-motivation-capability framework from the competitive dynamics literature, this paper develops a three-round framework that explores the evolution of the dynamic capabilities of domestic and foreign firms and the related competitive dynamics between them in (and eventually out of) transition economies. While previous research tends to focus on MNEs or domestic firms within transition economies, ours is one of the first efforts that systematically model the competitive interaction between them with a longitudinal perspective.